Enhancing Information Technology for Value Added Across Economic Sectors in Sub-Saharan Africa - Simplice Asongu; Mushfiqur Rahman; Joseph Nnanna; Mohamed Haffar (African Governance and Development Institute (AGDI), 2020)
This study investigates how enhancing information and communication technology (ICT) affects value added across sectors in 25 countries in Sub-Saharan Africa using data for the period 1980-2014. The empirical evidence is based on the Generalised Method of Moments. The following findings are established. First, the enhancement of mobile phone and internet penetrations respectively have net negative effects on value added to the agricultural and manufacturing sectors.Second, enhancing ICT (i.e. mobile phone penetration and internet penetration) overwhelmingly has positive net effects on value added to the service sector. From an extended analysis, enhancing ICT in the agricultural and manufacturing sectors should exceed certain thresholds for value added, notably: 114.375 of mobile phone penetration per 100 people for added value in the agricultural sector and 22.625 of internet penetration per 100 people for added value in the manufacturing sector.
Keywords: E23; F21; F30; L96; O55; 330; Economic Output; Information Technology; Sub-Saharan Africa